PENGARUH FAKTOR SOSIAL TERHADAP PENGAMBILAN KEPUTUSAN STUDI PADA SEKOLAH MENENGAH ATAS KATOLIK (SMAK) KOLESE SANTO YUSUF MALANG (HUA IND) - Sowanolo Halawa; Anni Yudiastuti; Cornelius Niwadolo (Universitas Katolik Widya Karya Malang, 2020)
The service sector which is growing rapidly in Indonesia, isthe education services sector. The development of privatehigh school in Indonesia led to increasingly fiercecompetition to win sympathy from prospective students whohave graduated junior high school (SMP) to choose the highschool that have been provided.This study aimed to: (1) to determine the significance ofsocial factors influence (X) consisting of the reference group(X1), family (X2), the role and social status (X3) for makingdecisions on studies in Catholic Senior High School (SMAK)Kolese Santo Yusup Malang (Hua Ind). (2) To determine thesocial factors that has the most dominant influence on thedecision-making studies at Catholic Senior High School(SMAK) Kolese Santo Yusup Malang (Hua Ind).The type of research is explanatory research. The populationis all male and female students who are studying in SMAKSanto Yusup Malang (Hua Ind) and sample in this studyconsist of 303 male and female students grade I to grade III.The data analysis is using multiple linear regression analysis.The results showed that 56.2% of male and female studentschose decision SMAK Santo Yusup Malang Colleges (Hua Ind)is influenced by social factors (X) consisting of the referencegroup (X1), family (X2), and the role and social status (X3 ),while the remaining 43.8% is influenced by other factorsoutside the social factor.Based on the results of F test and t test, we can know thatsocial factors (X) consisting of the reference group (X1),family (X2), and the role and social status (X3)simultaneously and partially has significant effect on thedecision on both male and female students in choosing SMAKSanto Yusup Malang (Hua Ind). The variables thatsignificantly influence the decision of male and femalestudents in choosing SMAK Santo Yusup Malang (Hua Ind) isthe role and social status (X3) with indicator influence healthclub (X21) and organizations such as OSIS (X22).